RANCANG BANGUN ROBOT BERODA PENGENAL WARNA PADA BOLA BERBASIS ARDUINO - Yusfrizal Yusfrizal (JTIK (Jurnal Teknik Informatika Kaputama), 2021)
The rapid development of technology, especially in the field of robotics, can be felt by all circles, technology is the result of an increasingly advanced human civilization, which greatly helps and makes it easier for humans to meet their daily needs. One of the wheeled robot technologies that have been successfully created today is a wheeled robot that is able to detect the color of a ball, but the object detection is still not perfect and there are still many shortcomings. This affects the path of the wheeled robot in the field, so it is necessary to improve the detection in order to better detect the color of the ball. In the design of a wheeled robot that recognizes the color of the arduino-based ball that is designed, the robot can look for the color on the ball according to the command on Android. The method used in this research is to use the method of observation and testing which is carried out by directly observing the situation in the room and conducting trials on the robot so that it can be seen the performance of the wheeled robot color recognition on the ball. The robot can search to recognize the color of the ball according to the command on Android, with a distance of 1 to 5 cm based on the trial scheme. In addition, the robot is also able to find the color of the ball according to the command on Android by following the position of the path that has been provided. The design of the wheeled robot to recognize the color of the ball using the TCS 3200 sensor based on Arduino with color input only detects 4 colors, namely red, green, blue, and black.